Randomized controlled trial of multidisciplinary team stress and performance in immersive simulation for management of infant in shock: study protocol. Issue 1 (December 2016) - Ghazali, Daniel; Ragot, Stéphanie; Breque, Cyril; Guechi, Youcef; Boureau-Voultoury, Amélie; Petitpas, Franck; Oriot, Denis
Abstract Background Human error and system failures continue to play a substantial role in adverse outcomes in healthcare. Simulation improves management of patients in critical condition, especially if it is undertaken by a multidisciplinary team. It covers technical skills (technical and therapeutic procedures) and non-technical skills, known as Crisis Resource Management. The relationship between stress and performance is theoretically described by the Yerkes-Dodson law as an inverted U-shaped curve. Performance is very low for a low level of stress and increases with an increased level of stress, up to a point, after which performance decreases and becomes severely impaired. The objectives of this randomized trial are to study the effect of stress on performance and the effect of repeated simulation sessions on performance and stress. Methods This study is a single-center, investigator-initiated randomized controlled trial including 48 participants distributed in 12 multidisciplinary teams. Each team is made up of 4 persons: an emergency physician, a resident, a nurse, and an ambulance driver who usually constitute a French Emergency Medical Service team. Six multidisciplinary teams are planning to undergo 9 simulation sessions over 1 year (experimental group), and 6 multidisciplinary teams are planning to undergo 3 simulation sessions over 1 year (control group). Evidence of the existence of stress will be assessed according to 3 criteria: biological, electrophysiological, and psychological stress. The impact of stress on overall team performance, technical procedure and teamwork will be evaluated. Participant self-assessment of the perceived impact of simulations on clinical practice will be collected. Detection of post-traumatic stress disorder will be performed by self-assessment questionnaire on the 7th day and after 1 month. Discussion We will concomitantly evaluate technical and non-technical performance, and the impact of stress on both. This is the first randomized trial studying repetition of simulation sessions and its impact on both clinical performance and stress, which is explored by objective and subjective assessments. We expect that stress decreases team performance and that repeated simulation will increase it. We expect no variation of stress parameters regardless of the level of performance. Trial registration ClinicalTrials.gov registration numberNCT02424890